2021
DOI: 10.3390/jcm10040698
|View full text |Cite
|
Sign up to set email alerts
|

Mesonephric-Like Adenocarcinoma of the Endometrium: Diagnostic Advances to Spot This Wolf in Sheep’s Clothing. A Review of the Literature

Abstract: Mesonephric-like adenocarcinoma is a recently described rare neoplasm occurring in the uterine corpus and ovary. This under-recognized subtype of carcinoma can be very challenging to diagnose. In mesonephric adenocarcinoma a variety of growth patterns can be present within the same tumor, as a result of which they can be misinterpreted and diagnosed as low-grade endometrioid adenocarcinoma, clear cell carcinoma, or even serous carcinoma and carcinosarcoma. We report a case of mesonephric-like adenocarcinoma mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 35 publications
(100 reference statements)
0
71
0
Order By: Relevance
“…It has been well known that uterine MLA has a poor prognosis with frequent metastasis, particularly to the lungs in nearly half of the metastatic cases [36]. In the largest multiinstitutional study by Pors et al [7], 58.1% (25/43) of the uterine MLAs were advanced FIGO stage (II or higher) tumors at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that uterine MLA has a poor prognosis with frequent metastasis, particularly to the lungs in nearly half of the metastatic cases [36]. In the largest multiinstitutional study by Pors et al [7], 58.1% (25/43) of the uterine MLAs were advanced FIGO stage (II or higher) tumors at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the immunostaining for ER and PR on MLA obtained in this study are quite heterogeneous, while most of the previously reported cases showed negative results [4,7,17,35]. Some authors have reported that the extent of hormone receptor positivity tends to be focal to patchy, with faint-to-weak staining intensity [5,36,37].…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have indicated that the prognosis of patients with uterine MLA is significantly different from that of patients with endometrial EC [4,7,10,35]. A multiinstitutional study confirmed that uterine MLA is a clinically aggressive tumor that typically presents at an advanced stage, with a predilection for recurrent pulmonary metastasis [10].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Treatment of endometrial MLA varies widely. Almost all patients undergo upfront surgery, but adjuvant treatments differ and include radiation therapy, hormone therapy, or chemotherapy; the optimal adjuvant treatment regimen remains unknown ( Deolet et al, 2021 ). The use of platinum-based chemotherapy regimens in the recurrent setting has shown mixed results ( Montagut et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%